1999
DOI: 10.1034/j.1399-3011.1999.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and structure–activity relationships of Ts κ, a novel scorpion toxin acting on apamin‐sensitive SK channel

Abstract: Tityus kappa (Ts kappa), a novel toxin from the venom of the scorpion Tityus serrulatus, is a 35-residue polypeptide cross-linked by three disulphide bridges and acts on small-conductance calcium-activated potassium channels (SK channels). Ts K was chemically synthesized using the solid-phase method and characterized. The synthetic product, sTs kappa, was indistinguishable from the natural toxin when tested in vitro in competition assay with radiolabelled apamin for binding to rat brain synaptosomes (IC50 = 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
(24 reference statements)
3
15
0
5
Order By: Relevance
“…According to what was demonstrated for previous studies on SK Ca channel-acting toxins, the positionsArg 6 , Arg 9 , Lys 18 and Lys 19 play a crucial role in its pharmacological activity (Lecomte et al, 1999). It was confirmed by binding assay and 1 H-NMR conformational analysis of the synthetic analogues that the Arg 6 residue and, to a lesser extent the Arg 9 residue, are responsible for a high-affinity interaction of this toxin with SK Ca channels.…”
Section: Accepted Manuscriptsupporting
confidence: 56%
See 2 more Smart Citations
“…According to what was demonstrated for previous studies on SK Ca channel-acting toxins, the positionsArg 6 , Arg 9 , Lys 18 and Lys 19 play a crucial role in its pharmacological activity (Lecomte et al, 1999). It was confirmed by binding assay and 1 H-NMR conformational analysis of the synthetic analogues that the Arg 6 residue and, to a lesser extent the Arg 9 residue, are responsible for a high-affinity interaction of this toxin with SK Ca channels.…”
Section: Accepted Manuscriptsupporting
confidence: 56%
“…A glance at the primary structure can help ( Figure 4A). According to point mutations and 1 H-NMR data above cited (Lecomte et al, 1999) the Arg 6 is mainly responsible for the high-affinity interaction of Ts9 with SK Ca channels, by creating a strong positive electrostatic interaction. The interaction of Ts9 with the SK Ca channel was modelled according to the charge anisotropy of the ligand and it was found that a basic surface, encompassing residues Lys 18 and Lys 19 on one side and Arg 9 and Tyr 8 on the other, would be in direct interaction with the channel (Blanc et al, 1997).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Both scorpions are found in desert regions of North Africa and the Eastern Mediterranean. Other more recently identified scorpion toxins that compete for apamin-binding sites with high affinity include toxin from the venom of the Central American scorpion Tityus serrulatus (12)(13)(14) and BmPO5 from the Asian scorpion Buthus martensii Karsch, widely distributed throughout China (15). Finally, toxins with greatly reduced binding affinities include PO1 and BmPO1 (15,16).…”
mentioning
confidence: 99%
“…Also has K + channel blocking action (Simpson et al, 1993) α-Tityustoxins (K + channel specific)* Polypeptides of 30-70 amino acids with three or four disulphide bridges. TsTx K-alpha contains 37 amino acids (Rogowski et al, 1992;Becerril et al, 1997) and TsTx kappa has 35 amino acids (Lecomte et al, 1999) 3.9 kD TsTx K-alpha reacts at an extracellular site on voltagegated non-inactivating K + channels. Toxin does not occlude pore (Werkman et al, 1993) Tricothecene mycotoxins (T-2)* T-2 has a tetracyclic sesquiterpene structure, including a six-membered oxygen-containing ring, an epoxide group in the 12,13 position and an olefinic bond in the 9,10 position.…”
Section: Mw Receptor Site(s)mentioning
confidence: 97%